Parenesis for the “Beloved” in a Threat of Faith and Salvation in the Epistle of Jude - Żywica, Zdzisław (Studia Warmińskie, 2021)
The author of the study answers the following questions. What does Judah want to say about the Addressees he describes as the beloved? What is the danger that he deemed it necessary to send them a Letter? What is their struggle for faith and salvation? Judah, while addressing to the addressees, gives them the honorable theological and ecclesial title Beloved, which is to remind them that God, guided by love and mercy, keeps them in vocation to eternal life through the saving mission of Jesus and wishes to renew in them their memory of the fundamental truth that The Church belongs exclusively to God and the Lord Jesus, not to any of his factions. All those who constitute the Church can only be servants of Jesus and brothers among themselves, faithfully keeping his Gospel handed down to them by the Apostles. The destructive danger to the Church and its saving mission appeared with the arrival of new teachers who rejected the grace of salvation, negating the truths and norms of the holiest faith. For this reason, they will certainly be subjected to judgment and punishment of eternal damnation, as well as those who let themselves be deceived. The only worthy answer of Jesus’ servant to the spreading blasphemous unbelief and godlessness is first, to immerse the Beloveds even deeper in God’s love, mercy, and peace through impeccable adherence to the doctrine and morality of the professed faith and sanctification by the power of the Holy Spirit in prayer. Secondly, to show mercy to those who doubt and already wander on the paths of ungodliness and after their conversion, to keep them in the community of the Church for their eternal salvation. Thirdly, they absolutely must condemn erroneous teaching and the blasphemous way of life of the wicked and exclude them from the community of the Church. But, when they have converted sincerely, they should also show mercy to them for the sake of ensuring the continuing saving mission of the Church and for their eternal salvation.